SYNTHESIS CHARECTERIZATION AND BIOLOGICAL EVALUATION OF ACYCLIC NUCLEOSIDE AND THEIR CONDENSED PYRENYL DERIVATIVES CONTAINING INDOLE MOIETY BEARING -2-THIAZOLIDINONE - S.MURALI KRISHNA,; P.RAVEENDRAREDDY,; L.K. RAVINDRANATH,; P.JAGADEESWARA RAO, (International Journal of Pharma and Bio Sciences, 2014)
This study is aimed to synthesize,characterize and screen the biological activity of a series of Synthesis of Synthesis of 1-((3-(3-(1,9-Dihydropyrene-6-yl)-4-oxo thiazolidin-2-yl)-1H-indol-1yl)methyl)-3-phenyl urea(10) was prepared by Indole-3-carbaldehyde and chloro ethyl acetate were dissolved in DMF.To this reaction mixture anhydrous K2CO3 was added and the reaction mixture was stirred at room temperature(350C) for 8 hours .To afford 2-(3-formyl1H-indol-1-yl)acetate(3). To this reaction mixture Equimolar quantity of 4,5-dihydro pyrene-1amine(4) were dissolved in absolute alcohol, to this three drops of aceticacid was added then heated on a steam bath for 5-6hrs at 1000C to obtain Ethyl2-(3-((1,9dihydro pyrene-6-yl imino)methyl)-1H-indol-1-yl)acetate(5).To this reaction mixture thioacetic acid and TEA,Dioxane was added and the mixture stirred at roomtemperature for 30min.compound Ethyl2-(3-(3-(1,9-dihydro pyrene-6-yl)-4-oxo thiazolidin-2-yl)-1H-indol-1-yl)acetate(6)was obtained. After hydrolysis to this reaction mixture isobutyl chloroformate (1:1eq) was added stirred for 30min, and aq NaN3 (3eq) was added and stirred for 20min at 00C.To obtain 2-(1(2-azido-2-oxoethyl)-1H-indol-3-yl)-3-(1,9-dihydropyren-6-yl)thiazolidin-4-one(8).The reaction mixture is treated with aniline(9) to obtain of 1-((3-(3-(1,9-Dihydropyrene-6-yl)-4-oxo thiazolidin-2-yl)-1H-indol-1-yl)methyl)-3-phenyl urea(10) was obtained. The structure of these newly synthesized compounds was characterised by 1H NMR,13CNMR ,Mass ,IR, and elemental analysis. The antimicriobial activity of the novel compounds was screened by agar disc diffusion method.